Antiproliferative activity and caspase enhancement properties of Annona muricata leaves extract against colorectal cancer cells (Faculty of Medicine Universitas Indonesia, 2016)
Background: The prevalence of colorectal cancer is rising in Asia including Indonesia. Annona muricata tea leaves, that is traditionally used for maintaining health, and lately being used by cancer patients. The objectives of this study is to investigate its effects in human colorectal cancer cell in vitro and ex vivo. Methods: Thirty patients with colorectal cancer (CRC) were enrolled in a randomized double-blind placebo-controlled trial. They were equally divided into two groups: those treated with 300 mg A. muricata leaf extract and placebo daily for 8 weeks. Serum from supplemented CRC patients of both groups was compared for caspase 9 and caspase 8 enhancement activity. Antiproliferative effect of water extract of A. muricata leaves and its fractions were evaluated against colorectal cancer cell line (DLD-1 and COLO 205) compared with 5-fluorouracil and placebo, the dose range was 62.5-2,000 μg/mL. Method used was 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Data were analyzed by Mann-Whitney U test. The p value was set at 0.05. Results: Ethanol-soluble fraction of A. muricata leaves extract water extract (ESFAM) leaves extract had cytotoxicity effects on DLD-1 as well as COLO 205 cell line, as shown by the lower IC 50 compared to 5-fluorouracil and placebo, 20.59 μg/mL and 654.9μg/mL, respectively. Serum of subjects supplemented with extract significantly induced caspase 9 (p=0.001) activity of DLD-1 colorectal cancer cell line, but not for caspase 8 activity (p=0.372). Conclusion: The study's results suggest the cytotoxicity potential of A. muricata leaves extract in in vitro and ex vivo studies.